Global land system maps at 1 km resolution for 1.5 °C climate - Yifan Gao; Haewon McJeon; Yang Ou; Li Chen; Jiaying Lv; Delin Fang; Yuanhui Wang; Sijing Ye; Changqing Song; Peichao Gao (Scientific Data)
Abstract Climate pledges are a key pathway for achieving temperature control but also exert profound cascading effects on the global Earth system. Evaluating such cascading effects often requires land change forecast products. However, current forecast products are all based on shared socioeconomic pathways (SSPs) and representative concentration pathways (RCPs). We proposed a comprehensive approach to generating 2100 land system maps under the 1.5 °C climate scenario and the baseline scenario by harmonizing the Global Change Analysis Model (GCAM), Globeland30, and the Land-N2N model. The maps exhibit a spatial resolution of 1 km and consist of 30 land system types, reflecting local high, medium, and low densities of land cover types. Additionally, we evaluated the Land-N2N using the kappa coefficient and figure of merit (FoM). The average kappa coefficient and FoM values across all the basins were 83.14% and 8.48%, respectively, demonstrating the reliability of the Land-N2N model in simulating land system changes. The dataset provides finer resolution quantitative support for global climate change mitigation and essential data for related research.